2007
DOI: 10.1073/pnas.0702401104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dioxygen enters the active site of 12/15-lipoxygenase via dynamic oxygen access channels

Abstract: Cells contain numerous enzymes that use molecular oxygen for their reactions. Often, their active sites are buried deeply inside the protein, which raises the question whether there are specific access channels guiding oxygen to the site of catalysis. Choosing 12/15-lipoxygenase as a typical example for such oxygen-dependent enzymes, we determined the oxygen distribution within the protein and defined potential routes for oxygen access. For this purpose, we have applied an integrated strategy of structural mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
139
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 32 publications
6
139
0
1
Order By: Relevance
“…The mutations strongly increase the Michaelis constant for H 2 , with no appreciable effect on the value of k cat (extrapolated to infinite concentration of H 2 in Table 1). This phenotype is expected when a mutation slows substrate access to the active site (4,5,8,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutations strongly increase the Michaelis constant for H 2 , with no appreciable effect on the value of k cat (extrapolated to infinite concentration of H 2 in Table 1). This phenotype is expected when a mutation slows substrate access to the active site (4,5,8,15).…”
Section: Discussionmentioning
confidence: 99%
“…In a few cases, however, mutations of some residues located in a putative gas channel did affect the enzyme's kinetic properties. For example, certain mutations in enzymes that use molecular oxygen as substrate increase the K m for O 2 (4,5,8,15). Brzezinski and coworkers (6) demonstrated that a glycine-to-valine mutation almost completely obstructs the oxygen channel of cytochrome c oxidase; in this study, the delayed access of substrate O 2 and inhibitor CO to the active-site heme was probed by using time-resolved UV-vis spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Recent developments in efficient computational sampling methods have allowed thorough scanning of the possible pathways for gas diffusion in the interior of proteins. [26][27][28][29] For example, such computational investigations have proved useful in understanding gas diffusion in many protein systems such as molecular dioxygen pathways via dynamic oxygen access channels in flavoproteins, [30][31][32] ammonia transport in carbamoyl phosphate synthetase, [33][34][35] and gas diffusion and channeling in hemoglobin. 28,36 In this paper, we use explicit solvent all-atom molecular dynamics (MD) simulations to investigate the protein barrel fluctuations in mCherry, which is one of the most useful monomeric variants of RFP.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive studies on their biochemical and molecular properties (Brash 1999;Saam et al 2007), this group of enzymes has not yet been introduced into industrial processes. Nevertheless, the specific activity of lipoxygenases to oxidize linoleic acid makes them interesting for applications in the papermaking process.…”
Section: B Oxidative Enzymesmentioning
confidence: 99%